Irrigation-energy tradeoff in water management of the Mahaweli River Basin, Sri Lanka - Udugama, P. K. B. A.; Tabucanon, Mario T.; Fujiwara, Okitsugu; Bogardi, Janos J.; The Royal Government of Belgium (Bangkok : Asian Institute of Technology, 1988)
This study presents an evaluation of economic benefits from irrigation and energy generation in the Mahaweli River Basin, Sri Lanka which consists of number of multipurpose reservoirs. The Mahaweli Development Project has been established to meet two main objectives, namely water supply for irrigation and hydroenergy generation . This analysis presents how the water can be best used between these two objectives. At the first stage of the analysis irrigation demands in the system were completely relaxed and then by imposing irrigation demands into the system by little degrees the performances of the system was observed in monetary terms. Depending on these observations minimum loss operation condition was found. Deterministic inflow data occurred in the past were used for the analysis. Data of three different kinds of years, namely dry year, wet year and average year were used. Mainly two mathematical models were developed in this study . They are IDP model for energy maximization from the power plants and GP model for supplying water for irrigation. The GP model was divided into two stages in order to determine final outcome from irrigation. Simplified configurations were used in solving both IDP and GP models. Rule curves for reservoirs in irrigation areas have also been developed as a result of this study. Analysis was performed for both 3-year and 1-year time horizons.
A thesis summitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Mahaweli Development Project; Hydroelectric power plants -- Sri Lanka